Pin pull-out behaviour for hybrid metal-composite joints with integrated reinforcements. (1st November 2016) - Nguyen, Alex T.T.; Brandt, Milan; Feih, Stefanie; Orifici, Adrian C.
Abstract: Hybrid metal-composite joints that integrate pins on the metal adherend are a novel joining concept, and knowledge regarding single pin performance and correlation to multi-pin joint behaviour is critically lacking. Here, we investigate Selective Laser Melting manufactured titanium with pins adhered to carbon fibre-reinforced polymer composite. Single pin specimens under pull-out loading and Mode I crack growth specimens were investigated using experimental, finite element (FE) and analytical methods. We found the pin-composite interfacial strength was 3.5 times higher than comparable carbon fibre z-pins due to excellent adhesion characteristics of the as-manufactured pin surface. Consequently, the pins enabled a 365% increase in Mode I steady-state fracture toughness. We also determined that the enhanced bonding increased the maximum pin load and Mode I initiation fracture toughness by around 250%, with no pin-composite debonding during cure. We lastly show FE models using the pull-out response characterised in single pin tests give excellent predictions of experimental behaviour in multi-pin joints with no additional calibration. The work provides new correlation between pin behaviour in isolation and in multi-pin joints, highlights the importance of strong pin-composite adhesion for joint performance, and demonstrates an analysis methodology suitable for design of pin-reinforced composites and metal-composite hybrid joints.